Reconciling the Tradeoff between Economic and Ecological Objectives in Habitat-Tree Selection: A Comparison between Students, Foresters, and Forestry Trainers. Issue 2 (3rd October 2018) - Cosyns, Hannes; Kraus, Daniel; Krumm, Frank; Schulz, Tobias; Pyttel, Patrick
Abstract: Habitat trees provide microhabitats for many forest-related species, and thus habitat-tree retention is one of the main measures to integrate nature conservation objectives into forests managed for wood production. By setting aside habitat trees, forest managers have to solve a crucial tradeoff between economic and environmental benefits. Therefore, it is of major importance that trees with desired characteristics are retained as habitat trees. In this study, we analyze habitat-tree selection. Specifically, we are analyzing the outcome of a habitat-tree selection exercise that took place in a so-called "marteloscope" or "tree marking training site" with silviculture trainers, district foresters, and forestry students. Our results show that participants consistently selected habitat trees with a low economic value. However, the habitat values of the selected trees were highly variable. Selection behavior depended on participants' expertise, with forestry trainers making more consistent decisions and outperforming the students as well as the foresters. Our results show that the selection of optimal habitat trees is not self-evident. We provide some ideas about how it can be improved, benefiting both ecological and economic forest management objectives.